Survey of Structural Relationship of Intellectual Capital, Psychological Empowerment, Organizational Learning and Performance - Ali Reza Ghaleei; Behnaz Mohajeran; Ali Abbass Miraghaie (Tehran University of Medical Sciences, 2018)
Background: This study aimed at investigating the structural relationship between intellectual capital, psychological empowerment, and organizational learning with staff performance of Tehran University of Medical Sciences in the form of a causal model. Materials and Methods: The research method was correlational type.  Data gathering was performed using four major scales including Benitez intellectual capital, Spreitzer Psychological empowerment, Neefe organizational learning, and Hersey & Goldsmith performance. A sample 450 of persons was selected using stratified method to test hypothesis and fitness of the proposed model. Data analysis performed using SPSS version 24 and Smart PLS software. Results: Data analysis indicated that measurement model, structural model and total model were fit. Intellectual capital, psychological empowerment, organizational learning had impact directly on performance 0.22, 0.30 and 0.45, respectively and the intellectual capital and psychological empowerment have indirectly impact on performance 0.27 and 0.26 respectively. Conclusion: Intellectual capital, psychological empowerment, and organizational learning have impact on performance directly. Also, Intellectual capital and psychological empowerment have impact on performance indirectly. Regarding to study finding, tailored programs and processes to promote Intellectual capital, psychological empowerment, and organizational learning status recommended.